Accounting for Natural Uncertainty Within Monitoring Systems for Induced Seismicity Based on Earthquake Magnitudes - Roy, Corinna; Nowacki, Andy; Zhang, Xin; Curtis, Andrew; Baptie, Brian (Frontiers in Earth Science, 2021)
To reduce the probability of future large earthquakes, traffic light systems (TLSs) define appropriate reactions to observed induced seismicity depending on each event's range of local earthquake magnitude (ML). The impact of velocity uncertainties and station site effects may be greater than a whole magnitude unit of ML, which can make the difference between a decision to continue (“green” TLS zone) and an immediate stop of operations (“red” zone). We show how to include these uncertainties in thresholds such that events only exceed a threshold with a fixed probability. This probability can be set by regulators to reflect their tolerance to risk. We demonstrate that with the new TLS, a red-light threshold would have been encountered earlier in the hydraulic fracturing operation at Preston New Road, UK, halting operations and potentially avoiding the later large magnitude events. It is therefore critical to establish systems which permit regulators to account for uncertainties when managing risk.